Stepping stone and option value in a model of postsecondary education - Nicholas Trachter (Quantitative Economics, 2015)
A stepping stone arises in risky environments with learning and transferrable human capital. An example is the role played by academic two-year colleges in postsecondary education: Students, as they learn about the uncertain educational outcomes, can drop out or transfer up to harder and more rewarding schools, carrying a fraction of the accumulated human capital. A theory of education is built and contrasted empirically to find that (i) option value explains a large part of returns to enrollment, (ii) enrollment in academic two-year colleges is driven by the option to transfer up, and (iii) the value of the stepping stone is small.
Keywords: 330; Stepping stone; investment under uncertainty; academic learning; postsecondary education; college education; returns to education